COVID-19 Misinformation Trends in Australia: Prospective Longitudinal National Survey - Pickles, Kristen; Cvejic, Erin; Nickel, Brooke; Copp, Tessa; Bonner, Carissa; Leask, Julie; Ayre, Julie; Batcup, Carys; Cornell, Samuel; Dakin, Thomas; Dodd, Rachael H; Isautier, Jennifer M J; et al. (JMIR Publications, 2021)
BackgroundMisinformation about COVID-19 is common and has been spreading rapidly across the globe through social media platforms and other information systems. Understanding what the public knows about COVID-19 and identifying beliefs based on misinformation can help shape effective public health communications to ensure efforts to reduce viral transmission are not undermined. ObjectiveThis study aimed to investigate the prevalence and factors associated with COVID-19 misinformation in Australia and their changes over time. MethodsThis prospective, longitudinal national survey was completed by adults (18 years and above) across April (n=4362), May (n=1882), and June (n=1369) 2020. ResultsStronger agreement with misinformation was associated with younger age, male gender, lower education level, and language other than English spoken at home (P<.01 for all). After controlling for these variables, misinformation beliefs were significantly associated (P<.001) with lower levels of digital health literacy, perceived threat of COVID-19, confidence in government, and trust in scientific institutions. Analyses of specific government-identified misinformation revealed 3 clusters: prevention (associated with male gender and younger age), causation (associated with lower education level and greater social disadvantage), and cure (associated with younger age). Lower institutional trust and greater rejection of official government accounts were associated with stronger agreement with COVID-19 misinformation. ConclusionsThe findings of this study highlight important gaps in communication effectiveness, which must be addressed to ensure effective COVID-19 prevention.